Resilience, Authentic Leadership, Employee Performance, and Intention to Leave Organization at PT Surya Indo Plastic, Sidoarjo - Mujiono Pangestu Alam; Dodi Putra Purnama; Siti Mujanah; AYA Fianto (Publikasi Indonesia, 2025)
Nowadays, the challenge of modern human resources is to retain potential talent to stay in the organization to build a strong organizational engagement and then achieve the organization's objective. The talent market has changed and the intention to leave employees is increasing in the organization. This study aims to prove and analyze the correlation between employee resilience, intervening by resilience, and moderating by authentic leadership on employee intention to leave the organization. Based on the correlation indicates talent management can apply a strategy to manage talent retain and achieve the organization's objective. Based on empirical data study the phenomenon that in the last 2 years 21 members of the leave organization was a critical issue to be analyzed and proving why the phenomenon raised and how to improve in the organization. This phenomenon researcher put two way perfective because employee and organization representative shall have a balance portion to be measure and analyze. The reference from the previous research can be found in the international journal, however, this research was subjective to an object of the specific organization with the limitation of external factors from outside the organization exclude for example job opportunities outside the organization, and personal factors from them employee itself notified as gaps in this research.